REALIZING SUSTAINABLE DEVELOPMENT GOALS VIA ENTREPRENEURIAL DIGITAL MINDSET: RESOURCE-BASED VIEW PERSPECTIVE - Corina Joseph; Saifulrizan Norizan; Tina Stephen Enggong; Mariam Rahmat; Chan Ai Nyet (International Journal of Accounting, Finance and Business, 2022)
Digitization is the way to go for entrepreneurs to survive during the post-pandemicrecovery era. The objective of this paper is first, to review the latest strategies related topromoting a digital mindset among entrepreneurs to stay relevant in this uncertain environmentand second, to suggest the importance of an entrepreneurial digital mindset as the intangibleresource using the Resource-based View Theory to sustain competitive advantage. This paperrecommends several actions that promote the digital entrepreneurial mindset i.e. 1) prioritizeopportunities, 2) continuously promote technological skills, 3) boost creativity and innovation,and 4) enhance agility and flexibility. This is among the first paper that conceptualizes theentrepreneurial digital mindset as an intangible resource. This paper also proposes ahierarchical model of the entrepreneurial digital mindset contribution to the business, national,and sustainable development goals.